Research progress on the role of oxidative stress in the development of diabetic bladder dysfunction - WANG Liyang; XUE Wei (Shanghai Jiaotong Daxue xuebao. Yixue ban)
Diabetes is a common endocrine and metabolic disorder, with its prevalence steadily increasing, particularly in China. It is often associated with a range of complications, among which diabetic bladder dysfunction (DBD) is prevalent but frequently overlooked, significantly impacting patients' quality of life. Although much is known about diabetes-related complications, the pathogenesis of DBD remains unclear. Recent studies have highlighted the critical role of oxidative stress in the development and progression of DBD. This review first introduces the relationship between oxidative stress and diabetic complications, detailing how oxidative stress is generated and its underlying mechanisms under hyperglycemic conditions. It then focuses on the link between oxidative stress and DBD, explaining how oxidative stress induced by diabetes leads to urothelial dysfunction, reduced detrusor muscle contractility, and neuronal degeneration, ultimately impairing bladder function. Recent animal studies have demonstrated promising results of antioxidant treatments in ameliorating DBD. Additionally, this review discusses the advances in antioxidant nanomaterials for the treatment of diabetic complications and their potential applications in DBD therapy. Based on these findings, the review aims to provide theoretical support for clinical research and guide future directions in antioxidant-based therapies for DBD.